2005
DOI: 10.1287/trsc.1040.0102
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Behavior at Bottlenecks

Abstract: Traffic operations in public walking spaces are to a large extent determined by differences in pedestrian traffic demand and infrastructure supply. Congestion occurs when pedestrian traffic demand exceeds the capacity. In turn, the latter is determined by a number of factors, such as the width of the bottleneck and the wall surface, as well as the interaction behavior of the pedestrians passing the bottleneck. This article discusses experimental findings of microscopic pedestrian behavior in case of bottlenec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
287
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 467 publications
(300 citation statements)
references
References 10 publications
13
287
0
Order By: Relevance
“…Several experimental and simulation studies have been performed to analyse the pedestrian flow characteristics in bottleneck with unidirectional and bidirectional flows. Hoogendoorn and Daamen [7] found that, with the increase in bottleneck width the capacity increases in a stepwise manner because of zipper effect. Whereas, Seyfried et al [8], Tian et al [30] shows that flow is linearly increasing with bottleneck width.…”
Section: Bottlenecksmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental and simulation studies have been performed to analyse the pedestrian flow characteristics in bottleneck with unidirectional and bidirectional flows. Hoogendoorn and Daamen [7] found that, with the increase in bottleneck width the capacity increases in a stepwise manner because of zipper effect. Whereas, Seyfried et al [8], Tian et al [30] shows that flow is linearly increasing with bottleneck width.…”
Section: Bottlenecksmentioning
confidence: 99%
“…So it may not be appropriate to adopt one region design values for the design of another region's pedestrian facilities. Many researchers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] have conducted considerable amount of studies on pedestrian dynamics and developed numerous models over the past decades. For developing these models, researchers adopted different approaches such as experimental, field and simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Bottlenecks are areas in which there is a significant capacity drop in pedestrian movement, such as a narrow doorway in a corridor, where jamming occurs when the incoming flow exceeds the capacity of the bottleneck (Seyfried et al, 2009). Hoogendoorn and Daamen (2005) observed that during such a jam, pedestrians form layers, and while trying to navigate through a door one metre wide, the width of these layers will become less than the effective width of a pedestrian, causing them to overlap. Effectively, when passing through a bottleneck, people come in close proximity, effectively moving into each other's personal space, which enables close contact such as getting within arm's reach of one another.…”
Section: Bottlenecksmentioning
confidence: 99%
“…However, reducing the number of people using the transport system or widening all bus doors is an unrealistic solution. Alternatively, other factors also influence crowding in a bottleneck, such as the behaviour of passengers passing through (Hoogendoorn and Daamen 2005). People's behaviour is influenced by their environment (Evans 2009).…”
Section: The Self-organizational Behaviour Of Crowdsmentioning
confidence: 99%
“…We consider a number of different experiments of varying complexity. More specifically, we consider two experiments: the crossing flow experiment from Hoogendoorn and Daamen (2005), and the merging flow experiment described in Haghani and Sarvi (2016).…”
Section: Experimental Analysesmentioning
confidence: 99%